Multi perspective ECG expert system - Aqel M.J.; Kak S.K. (My University, 2025)
The paper discusses an expert system developed to Interpret the electrocardiography (ECG) signal. The knowledge representation is based on frames and rules, the knowledge is stored in object structure where the frame is a class/instance representation. The system has the facility of modifying its perspective according to the user to accommodate his interest.